Individual ostracode valve analyses of Sclerocypris clavularis from modern Lake Turkana sediments - Measurements - Kaustubh Thirumalai; Andrew N Cohen; Dustin Taylor (PANGAEA, 2023)
This dataset contains measurements of individual ostracode valve analyses (IOVA), including stable oxygen (δ^1?O) and carbon (δ^1^3C) isotopes, and length/width, and mass measurements, at 17 sites across Lake Turkana, eastern Africa. These sediments were collected using a modified Ekman dredge during May–November 1979. The stable isotopic measurements were conducted at the [Paleo^2 Laboratory at the University of Arizonahttps://thirumalai.geo.arizona.edu/] on a Thermo Kiel IV Carbonate Device coupled to a 253 Plus IRMS; the length/width measurements were performed on a MeijiTechno HDZ7000TS Digital Zoom Microscope System, and mass of each valve was measured using a Sartorius Cubis II Ultra-Micro Balance. Details can be found in https://doi.org/10.1029/2022GC010790
In: Thirumalai, K et al. (2023): Individual ostracode valve analyses of Sclerocypris clavularis from modern Lake Turkana sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.958974